Determining fatal heart failure risks in patients diagnosed with chronic kidney disease: a machine learning approach - Haque, Adiba; Kabir, Anika Nahian Binte; Islam, Maisha; Monjur, Mayesha (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.